What Mechanisms Are Responsible for the Reuptake of Levodopa-Derived Dopamine in Parkinsonian Striatum? - Nishijima, Haruo; Tomiyama, Masahiko (Frontiers in Neuroscience, 2016)
Levodopa is the most effective medication for motor symptoms in Parkinson’s disease. However, various motor and non-motor complications are associated with levodopa treatment, resulting from altered levodopa-dopamine metabolism with disease progression and long-term use of the drug. The present review emphasizes the role of monoamine transporters other than the dopamine transporter in uptake of extracellular dopamine in the dopamine-denervated striatum. When dopaminergic neurons are lost and dopamine transporters decreased, serotonin and norepinephrine transporters compensate by increasing uptake of excessive extracellular dopamine in the striatum. Organic cation transporter-3 and plasma membrane monoamine transporter, low affinity and high capacity transporters, also potentially uptake dopamine when high-affinity transporters do not work normally. Selective serotonin reuptake inhibitors and serotonin and norepinephrine reuptake inhibitors are often administered to patients with Parkinson’s disease presenting with depression, pain or other non-motor symptoms. Thus, it is important to address the potential of these drugs to modify dopamine metabolism and uptake through blockade of the compensatory function of these transporters, which could lead to changes in motor symptoms of Parkinson’s disease.